Metode Pemahaman Hadis Jaringan Islam Liberal - Husaen Pinang (Jurnal Ilmiah Tarbiyah Umat, 2017)
The liberal Islamic Network is known as rasionalism community because considering a common sense as a main priority in understanding religious text. Hierarchically common sense is at the first position followed by Quran in the second, hadith in the third and ijma in the fourth, of course this positioning is entirely opposite to the growing insight that puts common sense under the Quran and hadith. This because they perceive that common sense has a plot to the truth and every religious text must be approached by common sense. Therefore everything including the Quran and the hadith can not be contradicted with common sense and if there is a conflict the common sense must be won. For Liberal Islamic Network there are many text of Quran and hadith that require reinterpretation because some text is no longer applicable in the present context. The reason for the impossibility of applying the religious text in contrary to the three thing, the first is human reason, the second is historical fact and the third is contemporary sosial condition. That is the three cases that guide this community in understanding the Quran and the hadith which then stretched to every text produced by the scholars. In this case the author explores the “littered” writings of Liberal Islamic Network leaders which is mixed in a more adequate presentation into a single unit. Considering the method of understanding this community against the hadith is not found in one of the works but dispersed and is segmentatif. By this writing it will examine form various books accompanied by several interviews, then certainly the author will complete the writing with various hadith an an example of the study.